MIDDLE CITY AND COLLECTIVE TRANSPORT SYSTEM: FEIRA DE SANTANA IN DEBATE - Reis, Ruy de Souza; Santos, Janio (Geosaberes; Vol 12 (2021)DO - 10.26895/geosaberes.v12i0.1126, 2021)
This article evaluates, based on the Urban Mobility Policy in Feira de Santana, the organization of the Collective Transport System, its characteristics and obstacles, to think how, based on the methodology, these services and logics are understood in medium cities. The methodology focused on mapping the collective transport network, applying buffer and bibliographic and documentary research. Feira de Santana is an example of how collective transport works in many medium cities in Brazil. Knowledge of the history of precarious services reveals fragments of the lives of the poor. Despite the importance of some laws, in practice, the true right to the city, including urban mobility, is a distant utopia.